1991
DOI: 10.1073/pnas.88.5.1893
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of DL-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid/quisqualate receptors by phospholipase A2: a necessary step in long-term potentiation?

Abstract: The effects of kainate (KA)-induced epileptic seizures on the binding properties of hippocampal glutamate receptors, on the modulation of DL-a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)/quisqualate receptor by phospholipase A2 (PLA2), and on the formation of long-term potentiation (LTP) were studied in hippocampal membranes and hippocampal slices. Systemic administration of KA (10 mg/kg; 15 hr survival) produced specific changes in the binding properties of the Although substantial progress ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 25 publications
2
35
1
Order By: Relevance
“…Added to this is the demonstration that AMPA receptors are sensitive to changes in the membrane/cytoskeletal environment in which they are embedded (Terramani et al 1988;Massicotte et al 1991;Hall et al 1992). In this context, the present observations are consistent with a view of LTP that regards ( 1 ) expres-…”
Section: Discussionsupporting
confidence: 81%
“…Added to this is the demonstration that AMPA receptors are sensitive to changes in the membrane/cytoskeletal environment in which they are embedded (Terramani et al 1988;Massicotte et al 1991;Hall et al 1992). In this context, the present observations are consistent with a view of LTP that regards ( 1 ) expres-…”
Section: Discussionsupporting
confidence: 81%
“…Inhibition of the PLA 2 -induced Modulation of AMPA Binding by the CSD Peptide-Because several studies indicate that calcium-dependent PLA 2 participates in selective changes in AMPA receptor properties (33,35), the previous results prompted us to examine the possibility that the inhibition of cPLA 2 activity could interfere with AMPA receptor binding. Double immunofluorescence was first used to examine whether caveolin-1 and AMPA receptors are co-localized at the cellular level.…”
Section: Cpla 2 Localization In Caveolin-rich Microdomains Andmentioning
confidence: 99%
“…Nevertheless, it is noteworthy that activation of the calcium-dependent enzyme phospholipase A 2 (PLA 2 ) could be part of the molecular mechanisms underlying changes in AMPA receptor conformation. In particular, it was reported previously that treatment of telencephalic membranes or tissue sections with exogenous PLA 2 or phospholipase C (PLC) heightened AMPA receptor affinity [39,40,41,42]. Various studies have suggested that the effect of phospholipases could be due to modifications of the lipid environment of the receptors, as incorporation of phosphatidylserine (PS) into rat brain membranes reproduced the increased affinity of AMPA receptors elicited by calcium-dependent phospholipases [43].…”
Section: Discussionmentioning
confidence: 99%